Reflections of an incentive reading project application in daily school context by the vision of the managers and teachers of the primary years in fundamental teaching (Research, Society and Development, 2019)
The present work has the objective to verify the reflexes of the application of an incentive project to the reading in the school context under the vision of managers and teachers of the Initial Years of Basic Education I of a municipal school located in the city of Santa Maria, in the state of Rio Grande do Sul. The research carried out is a case study of a qualitative nature. The sample consisted of seven participants, five of whom were class teachers and two managers. The data collection was carried out in 2017. The technique used was the structured interview. The results of the study point out that it is necessary to explore reading through reflexive practices, exercised in the classroom through questioning, analysis and discussion, stimulating the students' critical and reflective capacity, giving them exposure of ideas, subjective positions , and especially, the construction of meanings from what was introjected through reading. It is concluded that the projects to encourage reading in the daily school life can be considered as a potential agent thinking about the bias of Neuroscience, because they allow advances in the cognitive development of students who are observed in their critical and reflective posture in the classroom.